Assassination Classroom: Time for Sports Day - Vol 11 11, Victory! - Matsui, Yusei, 1981-; Miyaki, Tetsuichiro; Turnage, Bryant; Dutro, Steve (San Francisco, California : VIZ Media, LLC, 2016)
3-E student Isogai breaks the school rules by working part -time to help support his family. When Gakushu and rest of the Big Four students find out, they use his secret as leverage to force 3-E to participate in a bizarre sports- day competition. Soon its time for the schools midterm competition as well, but when some 3-E students accidentally injure the elderly owner of a day care/after- school program, Koro Sensei forbids them from studying and orders them to replace him until he recovers! Assassination is one thing, but babysitting little kids?
Rated T+ for older teen.
Translated from the Japanese.
Keywords: Assassination -- Comic books, strips, etc; Junior high school students -- Comic books, strips, etc; Extraterrestrial beings -- Comic books, strips, etc; Teacher-student relationships -- Comic books, strips, etc; Comic books, strips, etc. -- Japan; Translations into English; Graphic novels; Comics (Graphic works)